LIVING HADITS PENGGUNAAN BIDARA PADA MASYARAKAT KECAMATAN SILIH NARA, KABUPATEN ACEH TENGAH - Jannah Lukman; Hafizah Hafizah (IAIN Syekh Nurjati Cirebon, 2023)
Jujube is a plant mentioned in Qur’an as a plant in heaven. The use of jujube has been revealed in the Hadith of the Prophet. This study wants to explain how the knowledge of the Hadith of jujube in society and the practice of using jujube in daily life. The study focused on identifying the Hadith of jujube, the use of jujube and the benefits that have been felt by the people in Silih Nara Subdistrict, Central Aceh District. The study method used was literature and field studies which referred to the information from the informant and observation. There are 8 Hadiths related to jujube in the Main Source Hadith Book. It was found that people feel very happy using jujube regularly because they feel healthier and have a good effect on skin freshness. Apart from that, it is also used regularly for Islamic exorcism or treating bewitched diseases, taken as a medicine for fever, medicine for cholesterol and high blood pressure. The people also recommends that the crushed leaves of jujube are very good for treating wounds, rashes, itching and insect bites. The location of Silih Nara Subdistrict is suitable for planting jujube trees and has the potential to become a source of raw material for jujube or producers of jujube products. In the end, this study displays the glory of the Hadith and the practice of the Sunnah which are blessings for society.